2017
DOI: 10.5559/di.26.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Financial Satisfaction and Financial Literacy: Exploring Gender Differences

Abstract: The goals of this study were to explore gender differences in the components of financial literacy (financial knowledge, financial attitude and financial behavior) and financial satisfaction, and to explore gender differences in the relationship between financial satisfaction and the financial literacy components. Analyses conducted on a data collected on a large and heterogeneous sample of Croatian citizens (N = 900) showed that men scored higher on some financial literacy variables and were more financially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
16
0
4
Order By: Relevance
“…Income is an indicator applied to objectively access financial well-being in many studies that we reviewed (Avellar & Smock, 2005;Ozawa & Yoon, 2003;Pollock & Stroup, 1997;Salganicoff et al, 2009), whose results point to men having higher income than women. However, income is also approached as a sociodemographic element itself, playing a different role in perceived financial well-being per gender, being less important for women (Kirbiš et al, 2017;Warren, 2010). In a study that assessed the genetic and environmental influence of antecedent factors of financial well-being using a sample of twins, Zyphur et al (2015) identified that the effect of income on subjective financial well-being happens only for men and comes from social and nongenetic factors.…”
Section: Sociodemographicmentioning
confidence: 99%
See 2 more Smart Citations
“…Income is an indicator applied to objectively access financial well-being in many studies that we reviewed (Avellar & Smock, 2005;Ozawa & Yoon, 2003;Pollock & Stroup, 1997;Salganicoff et al, 2009), whose results point to men having higher income than women. However, income is also approached as a sociodemographic element itself, playing a different role in perceived financial well-being per gender, being less important for women (Kirbiš et al, 2017;Warren, 2010). In a study that assessed the genetic and environmental influence of antecedent factors of financial well-being using a sample of twins, Zyphur et al (2015) identified that the effect of income on subjective financial well-being happens only for men and comes from social and nongenetic factors.…”
Section: Sociodemographicmentioning
confidence: 99%
“…The assignment of distinct social roles for men and women, according to which the woman has primary responsibility for the care of children, the home and the family and the man is the main provider responsible for working and meeting the family's economic needs, affects women's work trajectory and their financial well-being. In addition, there is evidence that women are less financially literate than men (Al-Bahrani et al, 2020;Gerrans et al, 2014;Karakurum-Ozdemir et al, 2019;Kirbiš et al, 2017), more risk-averse in financial decision making (Borghans et al, 2009;Grable, 2000) and financially socialize later than men, who are involved at an earlier age in family financial discussions (Falahati & Paim, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals can also benefit from having an attitude that prevents them from worrying about (future) shortage of money (Kirbiš, et al, 2017). Positive future orientation, described as individuals' attitudes toward planning and providing for the future (Metcalf & Zimbardo, 2016), 1 is such an attitude.…”
Section: Future Orientation and Attitude Toward Moneymentioning
confidence: 99%
“…U Hrvatskoj postoji vrlo malo istraživanja razvijenosti i odrednica financijske pismenosti građana (npr. Vehovec, Rajh i Škrebin Kirbiš, 2015.;Škreblin Kirbiš, Vehovec i Galić, 2017.). Istraživanjem opisanim u ovom radu htjeli smo ostvariti dva glavna cilja.…”
Section: Uvodunclassified